Diplomatic Asylum in International Law: A Comprehensive Study of the Threshold of Diplomatic Asylum Between States - Hasan, Laura Kurniadi; Naftalie, Livia Aurelia; Gunadi, Ariawan (CV. Rayyan Dwi Bharata, 2025)
Diplomatic asylum represents a contentious area of international law, lying at the intersection of state sovereignty, territorial jurisdiction, and the humanitarian imperative to protect individuals facing persecution. This study explores the legal threshold for granting diplomatic asylum, focusing on the interplay between the rights of the host state and the obligations of the asylum-granting state. While the Vienna Convention on Diplomatic Relations (1961) establishes the inviolability of diplomatic premises, it provides no explicit provisions for asylum, resulting in a fragmented and inconsistent framework. The requirement for host state consent is analyzed as a critical factor in balancing sovereignty with humanitarian concerns, often leading to diplomatic tensions and breaches of international law. Moreover, the absence of enforcement mechanisms exacerbates the challenges in resolving asylum-related disputes.Through a detailed legal analysis, this study argues for the necessity of a multilateral treaty under the auspices of the United Nations to harmonize practices and establish clear norms governing diplomatic asylum. It also emphasizes the potential of regional cooperation in reducing conflicts and setting precedents for broader international frameworks. By addressing these gaps, this article aims to contribute to the development of a coherent legal regime that reconciles the competing interests of state sovereignty and individual protection.